Polymerase chain reaction evaluation for canine visceral leishmaniasis diagnosis in dog blood samples - Nunes, Cáris M [UNESP]; Dias, Ana Karina K [UNESP]; Gottardi, Fernanda Patricia [UNESP]; De Paula, Henrique B [UNESP]; De Azevedo, Márcia A A [UNESP]; De Lima, Valéria M F [UNESP]; Garcia, José Fernando [UNESP] (My University, 2007)
Canine and human visceral leishmaniasis is endemic in several States of Brazil, and it is associated with infected dogs and the presence of the vector. Aiming at using polymerase chain reaction as a diagnostic tool in dogs, we amplified a 120bp fragment from kDNA of Leishmania spp. by PCR in blood samples. The lower detection limit observed was 0.1 parasites per 500microL of blood, which is a highly satisfactory result. On the other hand, PCR evaluation in 166 blood samples of dogs from Poxoréo, MS, Brazil, resulted in 55% sensitivity and 66.3% specificity, considering indirect imunnofluorescent test as gold standard.
Avaliação da reação em cadeia pela polimerase para diagnóstico da leishmaniose visceral em sangue de cães.